PERAN FAKTOR KEPRIBADIAN EXTRAVERSION, NEUROTICISM PERSONALITY TRAIT TERHADAP PROBLEMATIC SOSIAL MEDIA USE PADA REMAJA AKHIR PENGGUNA TWITTER - Fatma Nurbaiti; Andi Tenri Faradiba; Aisyah Aisyah (JIVA : Journal of Behavior and Mental Health, 2022)
ABSTRACTExcessive use of social media has been associated with problematic behavior which caused by several factors such as personality trait. This study aims to investigate whether extraversion or neuroticism personality factors possess the role to problematic social media use (PSMU) who were at the late adolescence stage. The samples consisted of Twitter users aged 18-22 years (N=284) domiciled in Jakarta, and were collected by using opt-in panels online techniques via g-form. Instrument that used in this study is Social Media Use Questionnaire (SMUQ) (Xanidis & Brignell, 2016) to measure components of PSMU and Big Five Inventory-2 (Soto & John, 2017) to measure extraversion and neuroticism personality factors, and the analysis technique used is multiple linear regression. Finally, the results of this study acquired that neuroticism personality factor possess the significant role to compulsion dimension of problematic social media use. Then, the results also show that extraversion personality factor does not having a significant role to withdrawal and compulsion dimension of problematic social media use on late adolescence Twitter users. Another result of this study, shows that the use of Twitter in late adolescence is declared problematic, if the duration of using it 4- 5 or more than 5 hours (per-day).Keywords: extraversion, neuroticism personality factor, problematic social media use, Twitter, late adolescenceÂ ABSTRAKPenggunaan media sosial secara berlebihan, berkaitan dengan beberapa faktor seperti tipe kepribadian. Penelitian ini bertujuan untuk menguji apakah faktor kepribadian extraversion, neuroticism memiliki peran terhadap problematic social media use (PSMU) pada remaja akhir pengguna Twitter. Responden yang berpartisipasi pada penelitian ini merupakan individu usia remaja akhir 18-22 tahun (N=284) pengguna Twitter yang berdomisili di Jakarta, yang dikumpulkan dengan menggunakan teknik opt-in panels online, menggunakan instrumen Social Media Use Questionnaire (SMUQ) (Xanidis & Brignell, 2016) untuk mengukur problematic social media use yaitu withdrawal (reliabilitas item=0,85), serta compulsion (reliabilitas item=0,81), Big Five Inventory-2 (Soto & John, 2017) untuk mengukur faktor kepribadian extraversion (reliabilitas item=0,83) dan faktor kepribadian neuroticism (reliabilitas item=0,80). Teknik analisis data yang digunakan adalah multiple linear regression, menggunakan model SEM. Hasil penelitian didapatkan bahwa faktor kepribadian neuroticism memiliki peran yang signifikan terhadap dimensi compulsion dalam problematic social media use pada remaja akhir pengguna Twitter. Kemudian, didapatkan pula hasil penelitian bahwa faktor kepribadian extraversion tidak memiliki peran yang signifikan terhadap dimensi withdrawal dan compulsion dalam problematic social media use pada remaja akhir pengguna Twitter.Kata Kunci: faktor kepribadian extraversion, neuroticism, problematic social media use, Twitter, remaja akhir